Pengaruh Implementasi Balanced Scorecard terhadap Kinerja Keuangan dan Non-Keuangan pada Perusahaan Manufaktur - Rahman Wijaya (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Balanced Scorecard (BSC) is a strategic management tool used to measure organizational performance not only from a financial perspective, but also non-financial such as customers, internal business processes, and learning and growth. This study aims to analyze the effect of Balanced Scorecard implementation on financial and non-financial performance in manufacturing companies in Indonesia. The research method uses a quantitative approach with a survey of 100 managers and staff in various manufacturing companies. Data were analyzed using multiple regression to see the relationship between BSC implementation and organizational performance. The results showed that the implementation of the Balanced Scorecard had a positive and significant effect on financial and non-financial performance. BSC implementation helps companies align strategic objectives with operational activities, thereby increasing efficiency and effectiveness of performance. In addition, BSC encourages an organizational culture that focuses on continuous improvement. This study provides recommendations for manufacturing companies to adopt the Balanced Scorecard as a comprehensive performance measurement tool to achieve long-term competitive advantage.